2004
DOI: 10.1002/mds.20111
|View full text |Cite
|
Sign up to set email alerts
|

Survey on cannabis use in Parkinson's disease: Subjective improvement of motor symptoms

Abstract: An anonymous questionnaire sent to all patients attending the Prague Movement Disorder Centre revealed that 25% of 339 respondents had taken cannabis and 45.9% of these described some form of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 30 publications
6
93
1
2
Order By: Relevance
“…Venderova sent surveys to 630 patients attending a movement disorders clinic in Prague, and of the 339 respondents, 25 % had used marijuana. Of these 85 patients, 39 benefitted in rest tremor (31 %), bradykinesia (45 %), and dyskinesias (14 %), and continued its daily use [14]. A recent survey of Colorado residents with Parkinson using all types of complementary therapies found 9 using medical marijuana (4 %), reporting improvement of mood and sleep, but only 2 with improvement of motor symptoms, not specifically dyskinesias [15].…”
Section: Dyskinesias From Levodopa (In Advanced Pd)mentioning
confidence: 99%
“…Venderova sent surveys to 630 patients attending a movement disorders clinic in Prague, and of the 339 respondents, 25 % had used marijuana. Of these 85 patients, 39 benefitted in rest tremor (31 %), bradykinesia (45 %), and dyskinesias (14 %), and continued its daily use [14]. A recent survey of Colorado residents with Parkinson using all types of complementary therapies found 9 using medical marijuana (4 %), reporting improvement of mood and sleep, but only 2 with improvement of motor symptoms, not specifically dyskinesias [15].…”
Section: Dyskinesias From Levodopa (In Advanced Pd)mentioning
confidence: 99%
“…It acts via various mechanisms, such as inhibition of primary afferent nerve activity, decrease in neuronal response to a noxious stimulus, and inhibition of mast cell degranulation (Richardson, 2000). The effect of cannabinoid-related drugs on PD symptoms is still controversial (Sieradzan et al, 2001;Carroll et al, 2004;Venderov a et al, 2004;Chagas et al, 2014). A study from our Movement Disorders Clinic showed that treatment with medical cannabis was associated with a decrease in motor and pain scores as well as an improvement in sleep quality (Lotan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an early clinic report suggests no advantageous effects of cannabis on tremor among 5 unresponsive patients to anticholinergics and beta blockers [74]. By contrast, a questionnaire-based study revealed a 30.6 % improvement in rest tremor in tremulous [75]. A plausible argument for using cannabinoid agonists as therapeutic agents has arisen from studies describing the inhibitory effect of CB 1 R activation on glutamate release and its capability to oppose subthalamonigral neuronal overactivity and subsequently reduce tremor [64,76,77].…”
Section: Cannabinoids and Tremor In Pdmentioning
confidence: 99%
“…It has also been suggested that cannabinoid agonists and endocannabinoids can block dopamine transporters and thereby inhibit dopamine reuptake to ameliorate dyskinesia [78][79][80]. However, there are other studies asserting no beneficial effects of cannabinoid agonists in alleviation of motor symptoms [75,[81][82][83].…”
Section: Cannabinoids and Tremor In Pdmentioning
confidence: 99%